Effects of high-dose selenium-enriched Saccharomyces cerevisiae on growth performance, antioxidant status, tissue fat content and selenium concentration, and selenoenzyme mRNA expression in chicks - Gao, Shansong; Qiu, Huiling; Chen, Fu; Yang, Guoming; Hou, Lele; Dong, Jihong; Dong, Wenxuan (Poultry science, 2024)
Selenium-enriched Saccharomyces cerevisiae (SSC) as organic selenium (Se) has been shown to have better advantages and is approved for use in animal feed rather than inorganic Se, however, there is little available data on the toxic effects of SSC on poultry. The present study was conducted to investigate the effects of high-dose SSC on growth performance, antioxidant status, tissue fat content and Se concentration, and selenoenzyme mRNA expression in chicks. A total of 500, 1-day-old SPF chicks were randomly divided into 5 groups with 10 replicates of 10 chicks each. Group 1 served as a control and was fed a basal diet supplemented with 0.15 mg/kg Se from sodium selenite (SS), group 2 was fed the basic diet supplemented with 1.5 mg/kg Se from SS, while groups 3, 4, and 5 were fed the basal diet supplemented with 1.5, 5 and 10 mg/kg Se from SSC, respectively. The results showed that SS and SSC supplementation significantly affected the average daily feed intake (ADFI), feed/gain ratio (FCR), glutathione peroxidase (GPx) and superoxide dismutase (SOD) activities, total antioxidant capacity (T-AOC), malondialdehyde (MDA) content, tissue fat content and Se concentration, and GPx1 and GPx4 mRNA levels compared with the control group (P < 0.05). Compared with group 2, group 3 exhibited higher GPx and SOD activities, tissue Se concentration, and lower MDA content on d 30, and higher Se concentration, GPx1 mRNA levels in liver and breast muscle and GPx4 mRNA levels in liver and thigh muscle, and lower MDA content on d 60 (P < 0.05). The results of correlation analysis showed that high-dose SSC supplementation was positively correlated with AFDI, FCR, MDA content, and tissue Se concentration, and negatively correlated with GPx and SOD activities, T-AOC, GPx1 and GPx4 mRNA levels in tissues. In conclusion, up to 1.5 mg/kg Se from SSC in diet may be a safe concentration for chicks that exhibited better biological effects than SS, the toxic effects of high-dose SSC supplementation mainly exhibited growth decrease, peroxidation and lipid metabolism disturbance, and became stronger with the increase of dietary Se levels.